The ancient Egyptian book of the Moon : Coffin Texts spells 154-160 - Priskin, Gyula, (Archaeopress Egyptology ;, 2019)
This text proposes that Coffin Texts spells 154-160, recorded at beginning of the 2nd millennium BCE, form the oldest composition about the moon in ancient Egypt and, indeed, the world. The detailed analysis of these spells, based on a new translation, reveals that they provide a chronologically ordered account of the phenomena of a lunar month.